Evaluating Pharmacist’s Patient Care Process in Shiraz, using a newly-validated questionnaire: The First Report from Iran: Pharmacist’s Patient Care Process Indicators - Zare, Marziyeh; Zarei, Leila; Afifi, Saba; Karimzadeh, Iman; Ghaeminia, Mustafa; Peiravian, Farzad; Salehi-Marzijarani, Mohammad; Lankarani, Kamran B; Peymani, Payam (Acta Biomedica Atenei Parmensis, 2020)
Background: The Pharmacists’ Patient Care Process (PPCP) as one of many inter-related foundations for the delivery of evidence-based and outcomes-focused patient care has a positive trend in academic literatures in the world. Unfortunately, PPCP has not been establish well in community pharmacies in Iran, yet. This study was performed to explore the current status of the provision and perception toward patient care services and finally evaluate professional competency of pharmacists about PPCP implementation, in both patients and pharmacist’s perspectives. Methods: A cross-sectional study was conducted using two self-administrated Likert-based questionnaires_ one for pharmacists and another one for patients. In total, 121 pharmacists and 479 patients participated to the study. Questionnaires were distributed and collected in the Shiraz during the Oct 2017 till Jun 2018. Obtained data were analyzed through the statistical package for social sciences (SPSS) version 25. In addition, the competency to PPCP implementation was classified to three groups _good, moderate, and weak _ based on achieving ≥75%, 50%-75%, and